ANALISIS EFISIENSI PEMASARAN JAGUNG DI KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Hery Purwanto Manik; Rudi Febriamansyah; Mahdi Mahdi (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the structure, conduct and performance of the corn market in Sitiung District, Dharmasraya Regency. The research used a purposive sampling method, a sample of 50 farmers was selected as a respondent. The trader sample was carried out by following the flow of corn commodities from farmers to consumers. The research was conducted in December 2022-January 2023. Analysis of the market structure by analyzing the characteristics of the number of sellers and buyers, barriers, pricing ability and the types of products being traded. Analysis of market behavior by looking at the pricing system and the formation of prices between traders, selling and buying practices, and cooperation network systems between marketing agencies. Market performance analysis by calculating marketing margin and farmer's share. The results showed that the structure of the corn market has a tendency towards imperfect competition, namely oligopsony. Market conduct suggests that the final pricing system is a higher level marketing agency. Market performance shows that marketing channel II is assessed with the marketing channel with the highest level of efficiency because it has the lowest marketing margin percentage and the highest farmer's share.